Propuesta de aplicación de la metodología 5S en la industria láctea de Cotopaxi Inladec S.A. - Calispa Uyaguari, Yolanda Elizabeth (2023)
The present research was developed in the city of Salcedo in the province of Cotopaxi, in which it was proposed to generate a proposal through the fundamental principles of the 5s methodology, for the continuous improvement of the organization and cleanliness in the yogurt production area. , the project was developed in the company INLADEC S.A LÁCTEOS COTOPAXI, specifically in the production area, in which the main operators in charge of manufacturing were worked on and interviewed, extracting a database of the processes, including the production time. cycle and also, the main problems found in the area, in which through the use of direct observation techniques, 5s checklist and quality diagrams, it was possible to elucidate the process flow charts that take into account the rest time. of the product and the critical control points of the process were determined, generating an analysis of the initial state of the company including the most notable problems in it, also based on the experience of the workers and the on-site visits, a diagnostic evaluation of the the 5s in the area, to determine the degree of compliance that the company has, allowing the development of an overview of the institutional landscape and allowing the development of a focused proposal to support the strengths that the company has, generating an implementation proposal based on firm for the continuous improvement of the organizational culture and its durability over time, concluding in a process survey of 30 activities with a cycle time of 3223 mins, that the strong point of the organization is cleanliness where it has 76% of compliance, ending with a 5s application proposal focused on the continuous improvement of the process that contemplates specific methods for the preparation of the process, implementation of the methodology with formats and decision methods, as well as evaluations that allow controlling and monitoring implementation, in search of permanent and efficient long-term results in the company's yogurt production process.